A THEMIS:SHP1 complex promotes T‐cell survival. (22nd December 2014) - Paster, Wolfgang; Bruger, Annika M; Katsch, Kristin; Grégoire, Claude; Roncagalli, Romain; Fu, Guo; Gascoigne, Nicholas RJ; Nika, Konstantina; Cohnen, Andre; Feller, Stephan M; Simister, Philip C; Molder, Kelly C; et al.
Abstract THEMIS is critical for conventional T‐cell development, but its precise molecular function remains elusive. Here, we show that THEMIS constitutively associates with the phosphatases SHP1 and SHP2. This complex requires the adapter GRB2, which bridges SHP to THEMIS in a Tyr‐phosphorylation‐independent fashion. Rather, SHP1 and THEMIS engage with the N‐SH3 and C‐SH3 domains of GRB2, respectively, a configuration that allows GRB2‐SH2 to recruit the complex onto LAT. Consistent with THEMIS‐mediated recruitment of SHP to the TCR signalosome, THEMIS knock‐down increased TCR‐induced CD3‐ζ phosphorylation, Erk activation and CD69 expression, but not LCK phosphorylation. This generalized TCR signalling increase led to augmented apoptosis, a phenotype mirrored by SHP1 knock‐down. Remarkably, a KI mutation of LCK Ser59, previously suggested to be key in ERK‐mediated resistance towards SHP1 negative feedback, did not affect TCR signalling nor ligand discrimination in vivo. Thus, the THEMIS:SHP complex dampens early TCR signalling by a previously unknown molecular mechanism that favours T‐cell survival. We discuss possible implications of this mechanism in modulating TCR output signals towards conventional T‐cell development and differentiation.